Função das ações de Trade Marketing na construção ou manutenção do Brand Equity: um estudo de caso de uma marca de absorventes - Josko, Renata Borovina (2009)
About fifteen years ago, a phenomenon of retail concentration, an important and already consolidated movement in some European countries, started to occur in the Brazilian market. As a consequence, manufacturer s structures and relationships with retailers suffered great alterations. In relation to structure, there has been an increasing number of Trade Marketing departments in the companies and, investment in point of sale actions is growing steadily and has a significantly larger share in the total amount of brands investments. The manufacturer-retail relationship has become a zone of greater conflict and there has been a shift of power from the hands of manufacturers to those of retailers. Every year the market absorbs more and more brands and their extensions. The consumer is impacted by several product messages sent by expensive media, transforming brand equity maintenance or building into a constant challenge for the manufacturers. In addition to this situation there is a growing pressure for short term results, at precisely the moment in which investment in brand building, usually related to Advertising, is migrating to point of sale activities or is related to Trade Marketing. The main objective of the research is to acquire knowledge on the impact of Trade Marketing actions on Brand Equity. In order to achieve this objective, the case study methodology was used for an important external sanitary napkin brand in the Brazilian market. As a result, it was verified that the increasing amounts invested in Trade Marketing actions as opposed to amounts invested in advertising, have not helped maintenance and differentiate brand awareness and its associations in two different periods of the study